2015
DOI: 10.1089/neu.2014.3384
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prediction after Mild and Complicated Mild Traumatic Brain Injury: External Validation of Existing Models and Identification of New Predictors Using the TRACK-TBI Pilot Study

Abstract: Although the majority of patients with mild traumatic brain injury (mTBI) recover completely, some still suffer from disabling ailments at 3 or 6 months. We validated existing prognostic models for mTBI and explored predictors of poor outcome after mTBI. We selected patients with mTBI from TRACK-TBI Pilot, an unselected observational cohort of TBI patients from three centers in the United States. We validated two prognostic models for the Glasgow Outcome Scale Extended (GOS-E) at 6 months after injury. One mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 40 publications
8
114
2
3
Order By: Relevance
“…A considerable part of both the hospitalized and non-hospitalized patients were seen by surgeons and physical therapists, indicating that physical injuries might require attention up to six months after injury. The mean ISS was comparable with findings of the TRACK-TBI study, demonstrating that physical problems and related treatments are part of the heterogeneous mTBI spectrum [15]. Most outpatient contacts declined over time, however, those with psychiatrists/psychologists showed a consult rate of approximately 10% after six months, a figure which was also observed in a recent study among moderate and severe TBI patients [16].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A considerable part of both the hospitalized and non-hospitalized patients were seen by surgeons and physical therapists, indicating that physical injuries might require attention up to six months after injury. The mean ISS was comparable with findings of the TRACK-TBI study, demonstrating that physical problems and related treatments are part of the heterogeneous mTBI spectrum [15]. Most outpatient contacts declined over time, however, those with psychiatrists/psychologists showed a consult rate of approximately 10% after six months, a figure which was also observed in a recent study among moderate and severe TBI patients [16].…”
Section: Discussionsupporting
confidence: 82%
“…Yet, non-hospitalized patients were more often anxious, which might be related to uncertainty regarding the persistence of complaints [23]. The non-hospitalized patients, who are expected to make a full recovery and are not scheduled for regular follow-up, might feel a lack in opportunity to ask additional questions on expected recovery, despite the fact that an information leaflet was provided on discharge from the ED [10,15]. Whether intensified follow-up could help dealing with this uncertainty towards recovery is largely uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant factor that may affect test results following head injury, according to the work of Lingma et al [20], is PTSD. The number of participants in each group with a diagnosis of PTSD in their medical records is shown in Table 1.…”
Section: Potential Effects Of Individual Factorsmentioning
confidence: 99%
“…Notwithstanding the previous characterization of the pathophysiologic responses to TBI, these biologic responses occur in individuals who possess biologic differences that can modify their response to injury [53,108]. Over the last years, evidence has showed that the brain is capable of significant structural and functional repair, plasticity, and regeneration.…”
Section: Mechanisms Of Neural Injury In the Traumatic Penumbramentioning
confidence: 99%